Comparative analysis of the pivotal studies of extended half‐life recombinant FVIII products for treatment of haemophilia A. Issue 4 (6th May 2021) - Mannucci, Pier Mannuccio; Cortesi, Paolo Angelo; Di Minno, Matteo Nicola Dario; Sanò, Mario; Mantovani, Lorenzo Giovanni; Di Minno, Giovanni
Abstract: The need to reduce the burden of injections, and improve adherence and clinical outcomes in haemophilia A led to the development of recombinant FVIII products endowed with an extended plasma half‐life (EHL‐rFVIII) in comparison with standard half‐life products (SHL‐rFVIII). Lack of head‐to‐head studies makes difficult to grasp the relative value of each treatment option. We conducted a combined evaluation of the individual pivotal trials in order to assess between‐product differences regarding the reported efficacy results and FVIII consumption. We evaluated 4 EHL‐rFVIII products available to treat patients with haemophilia A without inhibitors and also a SHL‐rFVIII as a comparator. In the frame of these clinical studies, all the EHL‐rFVIII products showed a decrease in the injection burden coupled with good clinical efficacy, even though there were between‐product differences in terms of reduction in injection frequencies. Further, between‐product differences in terms of weekly/yearly consumption of rFVIII expressed in IU/Kg were identified, suggesting a different economic impact for the different EHL‐rFVIII products in the context of comparable clinical efficacy. The present findings based upon the review of pivotal studies done in the frame of a highly selected clinical scenario should be integrated with real‐life data.